Rhinocerebral Mucormycosis in Patients with Diabetes Mellitus After a New Coronavirus Infection (COVID-19): СT and MRI Patterns Data - I. S. Gabdulganieva; N. R. Munirova; A. R. Zaripova; V. I. Anisimov (Вестник рентгенологии и радиологии)
Objective: to study the computed tomography (CT) and magnetic resonance imaging (MRI) manifestations of rhinocerebral mucormycosis (RCM) in patients with diabetes mellitus and new coronavirus infection, to develop attentive attitude of radiologists for early detection of this pathology, rapid surgery and followup examinations.Material and methods. Totally 53 head (facial skull, soft facial tissues and brain) CT and MRI studies were performed in 13 patients with RCM. The number of CT and MRI studies varied from 1 to 9 per one patient, depending on the severity of his condition and clinical indications; the follow-up period was 1–4 months. All patients received surgical aid; diagnosis was verified by microscopy of surgical samples of excised necrotic tissues. A detailed descriptive analysis of pathological changes on CT and MRI characterizing RCM was carried out. The sequence of pathological signs manifestations was described, the prevalence of the lesion was estimated for planning the scope of surgical intervention. A comparative analysis of the identified RCM signs with the literature data was performed.Results. Lesions of the nasal cavity and paranasal sinuses in RCM were found in 100% of our observations, with approximately equal single and bilateral lesions of 54% and 46%, respectively. Lesions of the perimaxillar fatty tissue and pterygoid fossa were determined in 77% of patients, unilateral orbital lesions – in 23%, superior orbital vein and cavernous sinus thrombosis – in 31%, facial soft tissue lesion – in 15.5%, intracranial spread through the perineural spaces – in 7.7%, internal carotid artery arteritis – in 15.5%. Brain substance and meninges involvement in the pathological process was observed in the form of cerebritis in 23% of patients and meningitis in 46%. The formation of brain abscess was noted in follow up examinations in 15.5% of patients, skull bones osteomyelitis was diagnosed in 46%. The mortality rate was 15%. In cases of long-term observation, the manifestations of pathological changes started from the nasal cavity, then spreaded in the perimaxillary adipose tissue and orbit, and were followed by the development of intracranial complications.Conclusion. The accumulated experience in identifying the combination of CT and MRI signs and patterns of RCM combined with clinical and anamnestic data allows to increase the alertness of clinicians and radiologists for earlier diagnosis and selection of the optimal volume of surgical intervention.